2015
DOI: 10.1186/s40364-015-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

A striking response of plasmablastic lymphoma of the oral cavity to bortezomib: a case report

Abstract: BackgroundPlasmablastic lymphoma (PBL) is a rare and aggressive subtype of non-Hodgkin diffuse large B-cell lymphoma originally with a predilection to the oral cavity of patients infected with HIV. However, PBL of extraoral sites possesses clinicopathological characteristics distinct from oral PBL. Recently, therapeutic approaches using a proteasome inhibitor bortezomib to PBL of extraoral sites have been reported. We present a PBL patient with a bulky tumor of the oral cavity, who dramatically responded to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Reanalysis of our gene expression data (3 EBV + PT-PBL vs 20 EBV + PT-DLBCL, fold change 2, FDR < 0.05[ 95 ]) confirmed enhanced MYC signaling and demonstrated unfolded protein response endoplasmic reticulum stress signaling in PBL (unreported data). These findings provide an explanation for the success of bortezomib treatment in PBL case reports[ 96 , 97 ] and suggest that BET bromodomain inhibitors may represent a potential new therapeutic strategy, as has been successfully demonstrated in experimental models of multiple myeloma[ 98 ].…”
Section: Discussionmentioning
confidence: 94%
“…Reanalysis of our gene expression data (3 EBV + PT-PBL vs 20 EBV + PT-DLBCL, fold change 2, FDR < 0.05[ 95 ]) confirmed enhanced MYC signaling and demonstrated unfolded protein response endoplasmic reticulum stress signaling in PBL (unreported data). These findings provide an explanation for the success of bortezomib treatment in PBL case reports[ 96 , 97 ] and suggest that BET bromodomain inhibitors may represent a potential new therapeutic strategy, as has been successfully demonstrated in experimental models of multiple myeloma[ 98 ].…”
Section: Discussionmentioning
confidence: 94%
“…Similar features were reported in a previous case on oral cavity PBL with predominant centroblastic morphology. 35 Hirosawa et al 35 reported on a case of oral cavity PBL that showed proliferation of large cells with centroblastic morphology. The observation of predominant centroblasts in a case of gastrointestinal tract PBL in the current study has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Oral PBL shows a male predilection with 54.1 average age [9]. Plasmablastic lymphoma has been reported in the elderly patients who are not immuno-compromised [11,12].…”
Section: Discussionmentioning
confidence: 99%